1993
DOI: 10.2172/197141
|View full text |Cite
|
Sign up to set email alerts
|

Freeze concentration of dairy products Phase 2. Final report

Abstract: DISTRIBUTION OF THIS DOCUMENT 1s M m , , TEWand used to formulate products such as ice cream, cream cheese, milk chocolate and other products for consumer evaluation. Freeze-concentrated skim milk powder was reconstituted and compared against fresh skim milk as well as skim milk reconstituted from commercial liquid concentrate and nonfat dry milk powder for organoleptic quality and consumer acceptability. RESULTS The Niro PDU was successfully installed at Galloway West and brought up to 3-A processing standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…On the other hand, it was found that lactose had only a slight effect on the critical subcooling temperature for contact nucleation. The observation that whey proteins affect the rate of growth of ice crystals explains the results obtained by Best and Vasavada (1993) with whey permeate. If the critical subcooling temperature increases, it may also affect the microscropic structure of the crystal surface.…”
Section: Suspension Freeze Concentration Of Dairy Productssupporting
confidence: 65%
See 2 more Smart Citations
“…On the other hand, it was found that lactose had only a slight effect on the critical subcooling temperature for contact nucleation. The observation that whey proteins affect the rate of growth of ice crystals explains the results obtained by Best and Vasavada (1993) with whey permeate. If the critical subcooling temperature increases, it may also affect the microscropic structure of the crystal surface.…”
Section: Suspension Freeze Concentration Of Dairy Productssupporting
confidence: 65%
“…Two other lines of research, important for the application of cryoconcentration of dairy products, are the development of new equipment (Dickey et al, 1995;Zhang and Hartel, 1996;Habib and Farid, 2007) and the study of the influence of cryoconcentration on the proteins and lactose present in dairy products (Hartel and Chung, 1993). Best and Vasavada (1993) report the freeze concentration of skim milk, whole milk, sweet whey, whey protein concentrate and whey permeate using a single-stage configured Niro pilot plant unit ( Figure 1).…”
Section: Suspension Freeze Concentration Of Dairy Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993, Best and Vasavada's (1993) pioneer study on SFC equipment allowed to concentrate whole milk, skimmed milk, whey protein, and whey permeate. Due to the variable total soluble solids content of these dairy products, the maximum concentration (w/w) reached was 51% for whey permeate, 46.5% for whey protein, 44% for whole milk, and 40% for skimmed milk.…”
Section: Suspension Freeze Concentration In Dairy Productsmentioning
confidence: 99%
“…FC also offers an advantage in dairy processing by minimizing the heat abuse of sensitive milk components such as proteins and flavours (Sánchez et al, 2011b). Best and Vasavada (1993) have carried out an evaluation of FC in dairy processing. It has been reported that the organoleptic quality of freeze-concentrated milk fulfilled the quality of fresh skim milk and exceeded those of conventionally concentrated and powdered skim milks when reconstituted as a beverage or when used as an ingredient in the developing of cream cheese, frozen dessert, sour cream, salad dressings, whipped toppings and other products.…”
Section: Introductionmentioning
confidence: 99%